Hard Times, Times of Grace: The Church in the Face of the Pandemic - Martínez, Julio L. (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2021)
This article presents the challenges that the current pandemic, which is ravaging Humankind, poses to the Church. The focus is on the pastoral actions and attitudes necessary for those who carry out the priestly ministry, in areas such as accompaniment of the mourning of those who have lost loved ones, the processes of renewal and reform of life in the face of the impact of the disease, and the alteration of life that it produces, the socio-charitable, celebrative, educational, familiar, and defense needs of life, as well as the spiritual cultivation and foundations to respond evangelically to the harsh situation that we are enduring. The human experience from which it emanates stems from the all-encompassing phenomenon of COVID-19, and the Doctrinal framework is found in the Magisterium of Pope Francis, especially his latest Encyclical Fratelli tutti: On Fraternity and Social Friendship (2020), published several months after the outbreak of the pandemic, and also in Evangelii gaudium (2013). The Magisterium of the Cardinal Archbishop of Madrid will also have a significant place.
Keywords: pandemic; priests; parishes; crisis; discernment; Fratelli tutti; pastoral conversion; missionary conversion